Forests on fire : the fight to save our trees - Vogt, Gregory (New York : F. Watts, 1990)
Examines the devastating effects of forest fires and the various techniques used to combat and prevent them.
Includes bibliographical references and index.
Booklist.
School Library Journal.
Wilson's Senior High School.
8.1
8.1
Keywords: Fire ecology -- Yellowstone National Park -- Juvenile literature; Fire ecology -- United States -- Juvenile literature; Forest fires -- Government policy -- Yellowstone National Park -- Juvenile literature; Forest fires -- United States -- Prevention and control -- Juvenile literature; Forest fires -- Yellowstone National Park -- Juvenile literature; Ecology; Fire ecology; Forest fires; Ecology; Fire ecology; Forest fires; Yellowstone National Park -- Juvenile literature